Formation and development of the concept of social entrepreneurship - Bauer, M.Sh.; Bencheva, N.A.; Mussina, R.S. (BUKETOV BUSINESS REVIEW, 2019)
The development of civic activism and citizens' awareness of personal participation in events taking place within the state will lead to the formation of a prosperous and fair civil society. The interaction between the state and society is expressed in various forms, in particular in the idea of social entrepreneurship. The situation when the state is not able to provide all members of society with equal opportunities for self-realization in all areas can lead to the existence of social problems as an integral attribute of any society. If the needs of citizens are not satisfied and the growth of living standards and national welfare is not ensured we cannot talk about the effectiveness of modern socio-economic policy, because its main purpose is not fulfilled. In the modern world, social entrepreneurship is seen as a vector that determines the direction for eliminating or reducing urgent, pressing issues in various areas of the national economy, and solves the problems of finding people in difficult life situations. Social entrepreneurship as an activity is based on a social mission. Social entrepreneurship is a form of interaction between the state and society. Currently, there is no single approach to studying this problem. The article presents the development of theoretical aspects of social entrepreneurship. Based on the definitions given in the article, the characteristics of social entrepreneurship are described and identified. Stages in the history of the development of this phenomenon are highlighted; the main activities carried out by social entrepreneurs are considered; lists the main components and responsibilities of social entrepreneurship. The key advantages of a social enterprise are given.